Sistem Monitoring Dan Pengkabutan Otomatis Berbasis Internet Of Things (IoT) Pada Budidaya Jamur Tiram Menggunakan NodeMCU dan Blynk - Gunawan, Indra; Ahmadi, Hamzan (Fakultas Teknik Universitas Hamzanwadi, 2021)
The Mushroom is a wild plant and grow a lot in damp places, at the former rice bran and even grows on rotten trees. In the process of drying oyster mushroom it is very easy, only requires land for nurseries and maintains the temperature inside the oyster mushroom kumbung itself, for maintenance you must maintain the temperature and the humidity so that in the kumbung it remains moist and the oyster mushroom baglog not dry out because the temperature is not as required oyster mushroom baglog. So far, the cultivation that has been carried out is still manual, usually watering the oyster mushroom kumbung in the morning and evening, sometimes when it is hot during the day, watering is done to reduce the temperature inside the oyster mushroom kumbung. In this case the research was carried out on monitoring of temperature and humidity of oyster mushroom kumbung and automatic misting based on IoT which is combined with the blynk application which can be opened on an android smart phone by relying on an internert connection so that you can find out the temperature and humidity in the oyster mushroom kumbung This system uses a DHT11 sensor which functions to read temperature and humidity so that it sends data to NodeMCU V3 and then sends it to the user via the blynk application. If the temperature obtained is >30,200 the it will give a fog epek to the baglog automatically and the led in the blynk application will light up as a notification to the user that in the kumbung the oyster mushrooms are doing mist to lower the temperature of the kumbung and when the temperature is <=30.00 the fog will be stop and the led light in the blynk application will turn off, to be able to see the temperature and humidity of the oyster mushroom through the blynk application, you must first connect to the internet, both from the monitoring tool for oyster mushroom kumbung monitoring and automatic fogging based on iot or the smart phone user.